DISCOURSES ON ISLAM AND DEMOCRACY IN INDONESIA: A Study on the Intellectual Debate between Liberal Islam Network (JIL) and Hizbut Tahrir Indonesia (HTI) (JOURNAL OF INDONESIAN ISLAM, 2017)
This article discusses the relationship between Islam and democracy according to Jaringan Islam Liberal (JIL; Liberal Islam Network) and Hizbut Tahrir Indonesia (HTI). Using Critical Discourse Analysis (CDA), this article shows that according to JIL, Islam is compatible with modern democratic values. Democracy contains all modern governmental elements which are also found in Islam, such as consultation, consensus, justice, freedom, equality, and tolerance. Islam, in the view of JIL proponents, perfectly fits in line with modernity. Meanwhile, HTI argues that Islam is incompatible with democracy, because the word democracy comes from Western culture which means capitalist and secularist. Democracy is perceived by the HTI activists as a revolt against God’s sovereignty. These different views are influenced by their interpretation of Islamic values on the context of modern concept of democracy. In addition, this difference is also caused by the background of education, genealogy of knowledge, and condition of global politics.